2015
DOI: 10.1007/s12041-015-0503-3
|View full text |Cite
|
Sign up to set email alerts
|

Intersex (ix) mutations of Drosophila melanogaster cause nonrandom cell death in genital disc and can induce tumours in genitals in response to decapentaplegic (dpp disk ) mutations

Abstract: In Drosophila melanogaster, the intersex (ix) is a terminally positioned gene in somatic sex determination hierarchy and function with the female specific product of double sex (DSX(F)) to implement female sexual differentiation. The null phenotype of ix is to transform diplo-X individuals into intersexes while leaving haplo-X animals unaffected. This study on the effect of different intersex mutations on genital disc development provides the following major results: (i) similar range of a characteristic array… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…The earliest of these is ontogeny, which aimed at identifying the segmental origin of the different structures and how they sexually differentiate during development from the larval genital disc in D. melanogaster. It is thanks to this discipline that the 'traditional terminology' was established (Dobzhansky 1930;Ferris 1950;Bryant 1978) and continues to be used by contemporary developmental biologists (Chatterjee et al 2015). Most of the terms currently annotated in FlyBase (www.flybase.org) are based on the traditional system.…”
Section: Introductionmentioning
confidence: 99%
“…The earliest of these is ontogeny, which aimed at identifying the segmental origin of the different structures and how they sexually differentiate during development from the larval genital disc in D. melanogaster. It is thanks to this discipline that the 'traditional terminology' was established (Dobzhansky 1930;Ferris 1950;Bryant 1978) and continues to be used by contemporary developmental biologists (Chatterjee et al 2015). Most of the terms currently annotated in FlyBase (www.flybase.org) are based on the traditional system.…”
Section: Introductionmentioning
confidence: 99%
“…IX acts in concert with DSX to regulate terminal sexual differentiation (Garrett-Engele & Siegal et al, 2002). Yeast 1-hybrid and immunoprecipitation assays demonstrated that IX interacts with DSX F , but not DSX M (Garrett-Engele & Siegal, 2002;Siegal & Baker, 2005;Chatterjee et al, 2015). In D. melanogaster, ix has no introns, only a single mRNA transcript is detected (Siegal & Baker, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The earliest of these is ontogeny, which aimed at identifying the segmental origin of the different structures and how they sexually differentiate during development from the larval genital disc in D. melanogaster. It is thanks to this discipline that the 'traditional terminology' was established [2][3][4] and continues to be used by contemporary developmental biologists [5]. Most of the terms currently annotated in FlyBase (www.…”
Section: Introductionmentioning
confidence: 99%